Study of weight and height in newborns in multiparous women in Gorgan - MJ Gol Alipour (Babol University of Medical Sciences, 1999)
Objective: One of the common ways to study the infants’ growth in one society is evaluation of the anthropometric indices. The aim of this research is to find the average height and weight of the newborn babies in multiple in Deziani’s women hospital of Gorgan. Methods: This is a cross-sectional descriptive study on 1342 infants chosen randomly using the existing information in the hospital. Findings: The general average weight of the subject is 3330 grams, the average weight is 3371 grams in boys, and in girl infant the average is 3289 grams. The general average height of all the above newborn babies is 49.72cm, in boys it is 79.46cm and in girls 49.48cm. Our data shows that the average weight and height of boys is more than that of the girls (P=0.000). The average indexes of height and weight in those infants that were born by cesarean section are more than those born in a normal delivery. The above average indexes are higher among the infant from the urban comparing to those from rural babies, but these differences are not significant. The average weight in newborn infants in Torkaman race, and the average heights in newborn in Farsi race among the different sexes has a meaningful index. Our results show that the average weights and heights in different races are variable and there are significant differences between those (P<0.03). Conclusion: We have determined the anthropometric indexes in our area by this survey indicating the differenced by geographic and environmental conditions and races as well.